The Undergraduate Political Science Curriculum of International Islamic University Malaysia (IIUM): Translation of Integrated Political Science Curriculum Framework - Aziz, M. Abdul (NAJAHA, 2022)
Uplifting human moral values, social commitment and integrated personality is the core aim of education in addition to prepare graduates with professional skills and disciplinary knowledge. On that focus, the study developed the Integrated Political Science Curriculum Framework (IPSC) followed by mainly three approaches of educational research: philosophical, historical, and curriculum criticism. The IPSC model accommodated the courses on core disciplinary and faculty required courses, revealed knowledge, and generic skills. The proposed model was in response to growing scholastic debate on educational dualism and crisis of western education, devoid of moral and religious essence. The study mainly adopts library research and document analysis: previous curriculum models and university education frameworks, official documents, etc. In this article, the successful application of IPSC in the IIUM political science curriculum is rightly exemplified and indicates the relevancy of this in the multicultural society like Malaysia, Indonesia and Bangladesh.